STUDI KETERKAITAN ANTARA DIVIDEND PAYOUT RATIO, FINANCIAL LEVERAGE DAN INVESTASI DALAM PENGUJIAN HIPOTESIS PECKING ORDER. - A. Jatmiko Wibowo; F. Indri Erkaningrum (Faculty of Economics and Business, Universitas Gadjah Mada, 2002)
This study is aimed to examine the prediction of pecking order hypothesis in Indonesian. The hypothesis states that there is negative relationship between dividend payout ratio and investment. In addition, this study will learn the relationship between dividend payout ratio, financial leverage and investment. The dividend payout ratio determinants are financial leverage, investment, liquidity, profitability, size and variability of earnings. The financial leverage determinants are dividend payout ratio, investment, profitability, size, assets structure and variability of earnings. The determinants of investment are dividend payout ratio, financial leverage, sales growth, profitability, Q ratio and size.The data of this study is collected from 70 manufacturing companies as listed in the Jakarta Stock Exchange for the period of 1991 – 2000. The three stage least square simultaneous equation model is used to learn the relationship between dividend payout ratio, financial leverage and investment.In this study, it is found that there is no significant evidence that manufacturing companies in Indonesia tend to follow the pecking order hypothesis. In addition, it is found that the financial leverage gives a negative and significant influence on dividend payout ratio and vice versa; investment do not give a significant influence on dividend payout ration and vice versa; investment gives a positive and significant influence on financial leverage; and financial leverage do not give a significant influence on investment.Keywords: pecking order, dividend payout ratio, financial leverage, investment